Proposal and Evaluation of Vertical Vibration Theory of Air Caster - Tetsunoshin Ito; Mehrdad Sadeghzadeh Nazari; Kazuaki Inaba (Journal of the Civil Engineering Forum, 2024)
Urbanization and human development have increased the exposure of seismic risk. Therefore, engineers need to develop new and more efficient technologies to protect people and objects from the disastrous consequences of earthquakes. Air casters have gained attention and have been utilized in the past decade as effective seismic vibration control devices. Although such active isolation systems perform well in mitigating horizontal input vibrations, they might cause excessive rocking motions, if not designed properly. This fact emphasizes the importance of exploring the vertical dynamic properties of air isolation systems. To gain such an understanding, this research examines and proposes a formula for the vertical stiffness and damping of air caster systems. Theoretical solutions to the vertical stiffness and damping of such systems have been explored. Computer simulations considering fluid-structure interaction have also been performed to understand the dynamic behavior of the supporting air layer. Results have been compared to validate the proposed dynamic quantities within the considered simulation range. It is also concluded that the instantaneous air layer thickness, representing the air chamber pressure, and the bearing inlet flow rate are the key factors in determining the dynamic properties of the air layer. It is concluded that to evaluate the performance of the air caster seismic isolation device and increase the probability that the qualified seismic isolation performance will be exhibited, it is necessary to investigate which parameters are greatly involved in the viscous damping coefficient and the spring constant of  amass-spring-damper system equivalent to the air caster isolation system.